E-Health as a Service Software of Medical System in Prototype Modeling - Agus Nursikuwagus (Universitas Multimedia Nusantara, 2017)
Information system at community health center is an information system that has several activities, such as registration, medical record, health care, and reporting. Day to day operation, community health service, is using process manually. It is cause the stack of service. Sometime, the patient has to wait within several times. For Further, the patient did not know that the queuing is full. In order to help the problem, this paper wants to show about E-Health as service software. The research is completed by conveying the model like UML diagram. The UML diagrams are consisting such as usecase, class, activity, and component. The sequence of system construct is using Prototype Paradigm. The result is the software which has ability to service patient start from registration, medical check, medical prescription, until reporting. As an impact for Community health service is the service more efficiency. The system is able to control the medicine and reporting on day to day operation. REFERENCES[1] Susanto, Gunawan,” Sistem Informasi Rekam Medis PadaRumah Sakit Umum Daerah (RSUD) Pacitan Berbasis WebBase”. Pacitan. 2012.[2] B, Nugroho, S.H. Fitriasih, B. Widada, “Sistem InformasiRekam Medis Di Puskesmas Masaran I Sragen”. JournalTIKomSiN, vol.5, no.1, p.49-56, 2017.[3] G.G.S. Bagja,” Membangun Sistem Informasi KesehatanPuskesmas Cibaregbeg”, Univ. Komp. Indonesia, 2010.[4] A.M. Herdy, Aulia, M. Amran, D. Novita, “PerancanganSistem Informasi Pelayanan Medis Di Puskesmas SungaiDua”, STMIK MDP. 2014.[5] J. Sundari, “Sistem Informasi Pelayanan Puskesmas BerbasisWeb”, Int.Journal.on Soft.Eng, vol.2, no.1, p.57-62, 2016.[6] R.S. Pressman, Software Engineering A PractitionersApproach. Nineth Edition, Addsion Wesley, 2011.[7] G. Booch, J. Rumbaugh, I. Jacobson, Unified ModelingLanguage User Guide, Addison-Wesley, 1999.[8] I, Daqiqil. (2011, August 2). Framework CodeIgnite. [Online].Available: http://koder.web.id/buku-codeigniter-gratis/